COMPARATIVE ANALYSIS OF THE CONCEPT “WOMAN” IN ENGLISH AND UZBEK LINGUISTIC WORLDVIEWS (SCIENCE TIME JOURNAL, 2026)
This article examines the concept “woman” in English and Uzbek linguistic worldviews from a cognitive-linguistic perspective. Although both share a universal biological core, their interpretations differ due to cultural influences. In English discourse, the concept emphasizes individuality, autonomy, and evolving gender roles. In contrast, the Uzbek worldview presents women primarily through family roles, moral values, and social relationships. The analysis of lexical, phraseological, and literary data shows that the English model is more dynamic and flexible, while the Uzbek model remains more stable and tradition-oriented. The findings highlight the strong connection between language, culture, and cognition in shaping gender concepts.